Policy representation by the 2017 Bundestag - Andranik S. Tangian (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2017)
The paper estimates the policy representation of 34 German parties that have participated in the 2017 Bundestag (federal) election. For this purpose, the party positions on 31 topical issues are compared with the results of recent public opinion polls. Then we construct the party indices of popularity (the average percentage of the population represented) and universality (frequency in representing a majority). Regarding policy representation, the election winner, the conservative union CDU/CSU is ranked only 27th. The most representative among six Bundestag parties is the GRÜNE, constituting the smallest faction. In turn, the Bundestag indices of representativeness are about 40%, meaning that it is non-representative rather than representative. However, if the Bundestag were elected using 'the third vote', i.e. if the size of the Bundestag factions were made proportional to the indices of representativeness, it could significantly gain in policy representation.
urn:nbn:de:swb:90-755202
Keywords: D71; 330; policy representation; representative democracy; direct democracy; elections; coalitions